Visceral fat: the hidden culprit behind thoracolumbar surgery infections - Su, Dan; Wang, Ruiling; Li, Jucai; An, Xiaohui; Sun, Lingling; Cui, Yi; Zhang, Di (Frontiers in Surgery, 2025)
ObjectiveThis study aimed to explore the relationship between visceral fat area (VFA) and the risk of surgical site infection (SSI) after thoracolumbar posterior surgery.MethodsA retrospective analysis was conducted on 1,491 patients who had undergone posterior thoracolumbar surgery from January 1, 2022, through May 30, 2023. Inclusion criteria were age ≥18 years, undergoing thoracolumbar posterior surgery, and having complete clinical data with a follow-up duration exceeding 1 year. Exclusion criteria included minimally invasive surgery, preoperative infections, traumatic skin injuries, combined tumors, and patients with long-term steroid use or immune system diseases. VFA was measured using CT scans, and patients were categorized based on VFA ≥100 cm2 as having visceral fat obesity. The incidence of SSI was assessed according to the CDC criteria. Logistic regression analysis was used to identify risk factors for SSI.ResultsThe incidence of SSI was 2.4% (36 out of 1,491 patients). Multivariate logistic regression analysis showed that VFA was the most significant predictor of SSI [P < 0.001; Exp(B) = 1.026; 95% CI, 1.013–1.040], indicating a 2.6% increased infection risk per 1 cm2 increase in VFA. Other significant risk factors included BMI [P = 0.024; Exp(B) = 1.138; 95% CI, 1.018–1.273]. Patients with visceral fat obesity had a significantly higher infection rate (5.7% vs. 1.2%, P < 0.001).ConclusionVFA is a significant risk factor for SSI following thoracolumbar posterior surgery. Preoperative assessment of VFA can help identify high-risk patients and guide preventive measures to reduce SSI incidence and improve surgical outcomes.